Natural heritage of the Republic of Macedonia and manner of its protection - Zikov, Mihailo; Anastasovski, Vasil (Macedonian Journal of Ecology and Environment, 1993)
In this work are presented all natural districts and rural rarities in Macedonia given as natural inheritage. Besides the quantitive pointers to all spaces and objects of the natural rarities, in this work are given and specially valued the most important and protected by the law natural rarities. At the end are presented some of the ways of their protection as: zones for recreation, their special threating in space planning and their protection according to the law.